A string of phenomena : meta-ethnographic synthesis of qualitative studies and reviews of the advertising campaign of the 13th General Election in Malaysia - Mokhtar, Aida (Routledge, 2017)
The 13th general election in 2013 (GE13) was the most recent general election in Malaysia. It was a display of stiff competition as the main opposition coalition at the time, Pakatan Rakyat (PR), was a strong competitor for Barisan Nasional (BN), the ruling coalition. BN learned its lesson from the 12th general election campaign in 2008 (GE12) and came up with a large scale campaign and active participation on social media in GE13. The former prime minister of Malaysia who led the GE12 campaign, Abdullah Badawi, mentioned it was “a serious misjudgment” when BN depended on government- controlled newspapers and television as the opposition attracted young voters with mobile phone text messages and blogs for the elections (“Malaysian leader admits ignoring Internet was a mistake,” 2008). PR performed better in the election compared to the ruling coalition in GE12, increasing their seats from 19 to 82 in a parliament of 222 members. That election denied BN a two- thirds majority in the parliament. GE13 was regarded as the fi rst social media election by the new leader of BN at the time, Najib Tun Razak, because politicians from the two main coalitions used social media to engage with voters online (Lim, 2013 ; Sani, 2014 ). Gomez ( 2013 ) dispels this notion due to the BN’s poor election performance and described the election instead as BN losing the social media election. BN used both traditional and social media in the GE13 campaign (Bakar, Yusoff , & Hussin, 2014 ). Whichever view one takes, it is clear that the Internet has transformed the political communication style of Malaysian elections from the use of traditional mass media to a symbiosis of both traditional mass media for predominantly one- way communication and online media for interactive communication with voters. Of great interest to this chapter are the previous qualitative studies and reviews of the GE13 campaign in terms of advertising. A meta- ethnographic synthesis of qualitative research studies and reviews of the political campaigns for the 13th general election in Malaysia has generated themes and identifi ed keywords for comparison and contrast. These studies provide an insight into the GE13 campaign in relation to advertising. Before turning to the advertising in the GE13, it is important fi rst to understand the Malaysian populace and the country’s aspirations, which determine the signifi cant aspects of the election campaigns in GE13 and in previous elections.